Pemanfaatan Teknologi Digital: Efektivitas Edukasi dan Literasi Ekonomi dan Keuangan Syariah di Kota Bandung - Kurniawan, Fakhry Hafiyyan; Sobandi, Ade; Santoso, Budi; Maulana, Mahbub Afinini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The development of the sharia economy in Indonesia has not been carried out optimally, even though based on The Sate of Global Islamic Report (SGIE) 2023/2024 report, Indonesia is ranked 3rd out of several OIC countries which look at various aspects of the sharia economic and financial market sector as well as the halal value chain.. Therefore, in this research, a study was carried out on strategies for utilizing digital technology in the effectiveness of sharia economic and financial education and literacy in the city of Bandung. The number of respondents from this research was 481 people using the technique of distributing questionnaires and in-depth interviews. This research uses the TOWS approach or analysis. The results of this research show that the use of digital technology to increase understanding of sharia economics and finance can be optimized through a combination of "SO", "WO", "ST" and "WT" strategies. This strategy is obtained by combining internal and external potential or by filling each other's deficiencies with existing potential.